Effectiveness of Integration of Learning Strategies and Higher-Order Thinking Skills for Generating Ideas Among Technical Students - Mei Heong, Yee; Hie Ping, Kong; Jailani MD Yunos, Jailani; Widad Othman, Widad; Tee Tze Kiong, Tee; Mohamad, Mimi Mohaffyza; Kok Boon Ching, Kok (Journal of Technical Education and Training, 2019)
Learning strategies and higher-order thinking skills (HOTS) play an important role in higher education learning. Every student as different preferences and strengths in learning strategies and HOTS, thus it can be a stimulus for developing new ways of learning. The purpose of this research is to evaluate the effectiveness of the integration of learning strategies and HOTS in generating ideas via a self-instructional manual among technical students. This quantitative approach research used the modified quasi-experimental design with a treatment group (TG) and a control group (CG) comprising 81 students. The pre- and post-individual assignments and assessment analytic rubric were used as the research instruments. The pre- and post-assignments were used to test the effectiveness of the integration of learning strategies and HOTS in generating ideas before and after treatment was given to TG students. The assessment analytic rubric was used to evaluate the pre- and post-assignments based on five evaluation criteria (ideas, designs, functions, materials and dimensions). Each TG student received a self-instructional manual for the integration of Kolb’s learning strategies and Marzano’s HOTS as a treatment for one month, while the CG students had no treatment but conventional teaching. The gathered data were analysed using SPSS software. The findings show that there are statistically significant differences between TG and CG on the five evaluation criteria for the individual post-assignment result. There are also statistically significant differences in the five evaluation criteria between the individual pre- and post-assignments results. Overall, the approach of integrating learning strategies and HOTS by using a self-instructional manual for generating ideas is significantly effective.